1991
DOI: 10.1007/bf00280101
|View full text |Cite
|
Sign up to set email alerts
|

Impact of environmental and genetic factors on codeine analgesia

Abstract: The polymorphic cytochrome P-450 DB1 (P-450 IID6) is responsible for the O-demethylation of codeine to morphine by human liver microsomes. The influence of P-450 DB1 variable activity on the bioactivation of codeine in vivo to morphine and on its analgesic effect was investigated in phenotyped healthy volunteers--7 extensive [EM] and 1 poor [PM] metabolizer of debrisoquine. After pretreatment with oral placebo or quinidine sulphate 50 mg, codeine phosphate 100 mg or placebo were administered orally according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0
4

Year Published

1992
1992
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(110 citation statements)
references
References 27 publications
3
103
0
4
Order By: Relevance
“…In most individuals only a small fraction (ϳ10%) of codeine is metabolized to morphine via CYP2D6 (Caraco et al, 1996), with most being glucuronidated to codeine-6-glucuronide and the remainder being metabolized by CYP3A4 to norcodeine . The AUC of codeine is similar in PMs and in EMs (Yue et al, 1991;Mikus et al, 1997;Eckhardt et al, 1998), whereas morphine is virtually undetectable in PMs (Yue et al, 1991;Caraco et al, 1996;Poulsen et al, 1996b;Eckhardt et al, 1998), as well as in EMs taking quinidine (phenocopying) (Desmeules et al, 1991;Sindrup et al, 1992a;Caraco et al, 1996). Clinical studies in volunteers generally support the lack of analgesia in PMs, which is consistent with the belief that morphine is the key metabolite responsible for the antinociceptive effects of codeine (Desmeules et al, 1991;Sindrup et al, 1991;Poulsen et al, 1996b;Eckhardt et al, 1998).…”
Section: Antipsychoticsmentioning
confidence: 98%
“…In most individuals only a small fraction (ϳ10%) of codeine is metabolized to morphine via CYP2D6 (Caraco et al, 1996), with most being glucuronidated to codeine-6-glucuronide and the remainder being metabolized by CYP3A4 to norcodeine . The AUC of codeine is similar in PMs and in EMs (Yue et al, 1991;Mikus et al, 1997;Eckhardt et al, 1998), whereas morphine is virtually undetectable in PMs (Yue et al, 1991;Caraco et al, 1996;Poulsen et al, 1996b;Eckhardt et al, 1998), as well as in EMs taking quinidine (phenocopying) (Desmeules et al, 1991;Sindrup et al, 1992a;Caraco et al, 1996). Clinical studies in volunteers generally support the lack of analgesia in PMs, which is consistent with the belief that morphine is the key metabolite responsible for the antinociceptive effects of codeine (Desmeules et al, 1991;Sindrup et al, 1991;Poulsen et al, 1996b;Eckhardt et al, 1998).…”
Section: Antipsychoticsmentioning
confidence: 98%
“…Codeine, another widely available prescription opioid drug, derives its primary analgesic effect through metabolic conversion to morphine via the action of the CYP450 enzyme, CYP2D6 [47,48]. It is therefore expected that most patients taking codeine will have significant quantities of morphine in their urine; however, poor metabolizers may have significantly less or no detectable morphine.…”
Section: Codeinementioning
confidence: 99%
“…For example, depending on the allelic combinations of the highly polymorphic CYP2D6, patients are characterized as one of four phenotypes: poor, intermediate, extensive and ultrarapid metabolizers (8). Subjects who exhibit the poor-metabolizer phenotype will not convert codeine to morphine efficiently, and therefore will exhibit a reduced effect compared to patients who can form morphine (9). In addition to the important role these enzymes play in mediating opioid concentrations and responses, it has been suggested that biotransformation processes contribute to morphine tolerance secondary to induced enzymatic expression (10,11).…”
Section: Metabolic and Distributional Mediators Of Tolerancementioning
confidence: 99%